Interannual variability of transport and bifurcation of the North Equatorial Current in the tropical North Pacific Ocean - 翟方国 胡敦欣 (Chinese journal of oceanology and limnology, 2012)
The relationship of the interannual variability of the transport and bifurcation latitude of the North Equatorial Current (NEC) to the El Niño-Southern Oscillation (ENSO) is investigated. This is done through composite analysis of sea surface height (SSH) observed by satellite altimeter during October 1992–July 2009, and correspondingly derived sea surface geostrophic currents. During El Niño/La Niña years, the SSH in the tropical North Pacific Ocean falls/rises, with maximum changes in the region 0–15°N, 130°E–160°E. The decrease/increase in SSH induces a cyclonic/anticyclonic anomaly in the western tropical gyre. The cyclonic/anticyclonic anomaly in the gyre results in an increase/decrease of NEC transport, and a northward/southward shift of the NEC bifurcation latitude near the Philippine coast. The variations are mainly in response to anomalous wind forcing in the west-central tropical North Pacific Ocean, related to ENSO events.